Praktik Supervisi Pendidikan dalam Pendidikan Anak Usia Dini - Risnajayanti (MUNTAZAM, 2023)
The success of Early Childhood Education depends not only on the competence of educators, but also on the effectiveness of the educational supervision system implemented. The research investigates the practice of educational supervision in Early Childhood Education through literature study. The objectives of the study include exploration of the purpose of supervision, the application of supervision practices, teachers’ perceptions of supervision, and the challenges and impacts of supervision practices. Through literature analysis from various sources, this study summarizes findings related to supervision practices in the context of Early Childhood Education. Although the method focuses on literature study, this research still provides aspects insight into key aspects related to the practice of educational supervision. The implications of these findings are discussed to contribute to the development of more effective supervision practices and have a positive impact on teachers’ professional development and improvement of learning quality.